Strategi pengelolaan sampah anorganik di Pasar Kebayoran Lama Jakarta - Shafira, Rizka; Elfidasari, Dewi; Nurhasanah, Nunung (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
Traditional markets contribute 14.48% of national waste generation. This study aims to formulate an inorganic waste management strategy for Kebayoran Lama Market Area 11, Jakarta. A mixed-methods approach was applied involving 150 respondents (75 traders and 75 consumers) and waste generation measurements over eight consecutive days (SNI 19-3964-1994) from 26 traders out of 698. The results showed that the average inorganic waste generation from the sample was 3.014 kg/day, which extrapolates to 80.91 kg/day for the entire market, dominated by plastic (70%). The reduction potential through mass balance analysis reached 79% (2.381 kg/day from the sample). Traders' understanding of national regulations (Law No. 18/2008) was very low (16%), while consumers demonstrated higher understanding (37.4%). The Mann-Whitney test indicated no significant difference in participation perception between the two groups (p = 0.3315). Multi-criteria evaluation using PROMETHEE established priority strategies: provision of segregated 3R waste bins (Φ+0.5300), revitalization of the waste bank (Φ+0.2500), and education programs (Φ+0.1400). The novelty lies in integrating mass balance, non-parametric statistics, and multi-criteria decision-making. These strategies have the potential to increase residue reduction by up to 90% and support circular economy development.